Penetapan Hak Asuh Anak Yang Belum Mumayyiz Kepada Ayah Perspektif Maqashid Syari’ah (Analisis Putusan PTA Padang No.18/Pdt.G/2022/PTA.Pdg) - Azmi, Muhammad Nurul; Khalid, Khalid (Universitas Ekasakti, 2023)
The impact of divorce must be very significant for a child, especially if the child is still underage. A child needs the affection, attention and supervision of both parents. This research aims to explore the custody of children to fathers according to the Islamic Law Compilation and the Shariah Maqashid perspective. In this study the author uses a qualitative method of normative jurisprudence. According to the results of research that has been carried out in the Compilation of Islamic Law, the custody of a child who has not been fully mumayyized is the right of the mother. But when the child is self-sufficient and can distinguish between good and bad, then the child can be categorized as already mumayyiz. Then the child has the right to decide to whom he will be raised.